Space-confined growth of novel self-supporting carbon-based nanotube array composites. (15th March 2019) - Dang, Liyun; Hou, Yubin; Song, Chuang; Lu, Qingyi; Wang, Ze; Feng, Qiyuan; Lu, Qingyou; Gao, Feng
Abstract: Tube-like nanostructure, especially carbon nanotube, usually has distinguished properties, making itself useful substrate for producing hybrid and composite materials with various applications. In this study, we proposed a space-confined self-oriented reaction in a single-ended reactor for the directional-induced decomposition of plate-like Zn-Fe double metal cyanide nanostructure. Two novel different kinds of magnetic self-supported carbon-based nanocomposites, FeC nanoparticle@ZnCN2 nanotube composite and austenite/Fe nanoparticle@carbon nanotube composite, were respectively synthesized. These nanotubes subjected to the plate-like precursor were short and non-intertwined, unlike most carbon nanotubes reported before. It was found that reactor geometry plays key roles in the self-oriented growth of these carbon-based nanoarrays and fine tubular reactors with different reducing aspect ratio (AR) values result in different nanocomposite products.